Determination of relative sensitivity factor, sputtering rate, and detection limits of deuterium in deuterium ion‐implanted Zircaloy‐4 using secondary ion mass spectrometer. (8th August 2022) - Singh, Manish; Karki, Vijay; Jaison, Perumpillil G.
Abstract : Zirconium‐based alloys are extensively used in the nuclear industry as materials for reactor core components. These alloys are used in fuel cladding and pressure tubes with 1 H2 O or 2 H2 O as the primary heat exchange fluid. Continuous usage of pressure tubes and fuel cladding inside the reactor results in heavy ingress of hydrogen ( 1 H) or deuterium ( 2 H), which gives rise to the formation of hydrogen (or deuterium) precipitates in the host of zirconium matrix. This is called hydrogen (or deuterium) embrittlement phenomenon. Therefore, determination of hydrogen or deuterium concentration periodically in zirconium alloy pressure tubes and cladding are crucial for safe operation of nuclear reactors. Hence, in this work, secondary ion mass spectrometry (SIMS) has been utilized to determine the relative sensitive factor (RSF), sputtering rate, and detection limits of 2 H in 2 H + ion‐implanted Zircaloy‐4 sample. SIMS analysis has been carried out using O2 + and Cs + primary ion beams. Depth profiles of various elemental and molecular secondary ions have been monitored to determine the RSF values and detection limits of 2 H in the sample under different primary ion beam analysis conditions. Sputtering rate under different analysis conditions has also been determined from the correlation between the projected range of 2 H + ions in Zircaloy‐4 sample determined from Stopping and Range of Ions in Matter (SRIM) software and the depth of the crater formed by primary ion beam bombardment process. The projected range of 2 H + ions in Zircaloy‐4 was estimated to be ~524.2 nm using the simulation carried out by SRIM software. The projected range, evaluated by SRIM software, was utilized for depth scale calibration of SIMS sputtered time profiles. The SIMS depth profiles were also calibrated by determining the depth of the SIMS crater by using optical depth profilometer. The values of range estimated by SRIM as well as optical profilometer were found to be in good agreement, within instrument uncertainty.